Clinical performance of indirect esthetic inlays and onlays for posterior teeth after 40 months - Regina Helena Barbosa Tavares Silva; Ana Paula Dias Ribeiro; Alma Blacida Conception Elisaur Catirze; Lígia Antunes Pereira Pinelli; Laisa Maria Grassi Fais (Universidade Estadual de Campinas, 2015)
Aim: Searches for biocompatible restorative materials with better clinical properties, longevity and esthetics have resulted in the development of several ceramic types. The aim of this study was to evaluate the performance of Ceramco inlays and onlays over 40 months. Methods: Thirty ceramic indirect restorations were placed in 10 patients and all were adhesively cemented with a dual resin cement. The clinical performance was evaluated by a calibrated examiner who attributed scores adapted from the Cvar and Ryge criteria: color, marginal adaptation, abrasion, caries recurrence, fracture and postoperative pain. These assessments were performed after cementation of the restorations (T0 =baseline) and after 4 periods: T1 (10 months), T2 (20 months), T3 (30 months) and T4 (40 months). Photographs were made in T0 and T4 to illustrate the general condition of each restoration. Data were analyzed statistically by Kruskal-Wallis H statistics (p=0.05) and results were presented using percentage values. Results: Clinical evaluation revealed no color alteration or abrasion (100%); a success rate of 96.7% for caries, fractures and postoperative pain; and 76.7% of failure for marginal adaptation. Conclusion: The ceramic restorations did not show alterations that could result in their replacement, although there was a moderate failure in the marginal adaptation.